2007
DOI: 10.1017/s0033822200042545
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of Key Barrows Belonging to Different Stages of the Scythian Period in Tuva (Arzhan-1 and Arzhan-2 Barrows)

Abstract: This paper focuses on the chronological study of 2 Scythian period monuments that are the key to the chronology of the entire Eurasian Scythian culture. These are the unique monuments of Arzhan-1 and Arzhan-2 in Central Asia (Tuva Republic). The dating of both these monuments began immediately after their discovery, but discussion about their chronological position is still current. Both monuments contained considerable wooden material from their construction suitable for dendrochronology and radiocarbon datin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 5 publications
(6 reference statements)
0
17
0
Order By: Relevance
“…795-815 cal. BCE (42), coeval with the end of the DSK period (7). In Mongolia itself, metal bits first enter the archaeological record in the Early Iron Age, via burials of the Slab Burial or Duruvljin Bulsh culture (33).…”
Section: Discussionmentioning
confidence: 99%
“…795-815 cal. BCE (42), coeval with the end of the DSK period (7). In Mongolia itself, metal bits first enter the archaeological record in the Early Iron Age, via burials of the Slab Burial or Duruvljin Bulsh culture (33).…”
Section: Discussionmentioning
confidence: 99%
“…Arzhan 1 is a complex funerary monument; a ‘royal’ barrow containing over 160 horse skeletons (Gryaznov, 1980; Bourova, 2004; Bokovenko, 2006). The barrow is considered to be the earliest ‘Scythian’, or ‘pre‐Scythian’, monument in Eurasia, dating to the boundary of the 8th and 9th centuries BC (Zaitseva et al ., 2007). Only a small part of the original collection of horse skeletal material excavated from Arzhan 1 has been retained.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on stylistic reasons, it was argued that this was one of the earliest appearances of the so-called "Scythian triad" consisting of weapons, horse gear, and objects in Scythian animal style dating to the late 9th/early 8th century BCE [1] (p. 72). This has since been scientifically confirmed by a number of radiocarbon dates [2]. Thus, first millennium horseback pastoralism was attributed to an emergence in the eastern Eurasian steppes, a hypothesis since supported by a number of studies, most recently [3].…”
Section: Introductionmentioning
confidence: 74%
“…To this date, it remains the richest burial of Early Iron Age nomadic pastoralists ever found, with several thousand gold items in a rarely seen quality of craftsmanship [5]. Arzhan 2, dating to the 7th century BCE [2], showed that the Uyuk Valley in Tuva Republic remained an important place for burials of the social elite during much of the first millennium BCE. In 2017, a Russian Swiss expedition surveyed and dated the large burial mound Tunnug 1 to the 9th century BCE, finding another monument dating to the time of the Late Bronze Age-Early Iron Age transition in the eastern Eurasian steppes [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation